Low-cobalt ternary positive electrode material and preparation method and application thereof

CN122992043APending Publication Date: 2026-10-27TIANJIN B&M SCI & TECH LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611333497.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]现有技术常采用高钴前驱体与氢氧化锂烧结制备三元正极材料,由于三元前驱体钴含量较高,钴资源有限且价格昂贵,制备成本较高;钴含量高会增加材料循环或存储过程中钴溶出量,导致材料结构退化失效;采用常规工艺烧结,三元正极材料缺陷多,性能略差

Benefits of technology

1.本发明低钴三元正极材料,可以有效降低Co含量,降低材料制备成本;通过低Co含量的基体结合Co包覆层和快离子导体包覆层,在降低成本的同时,优化材料结构和保证电化学性能优异,拥有高容量且低阻抗的特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992043A_ABST
    Figure CN122992043A_ABST
Patent Text Reader

Abstract

The application provides a low-cobalt ternary positive electrode material and a preparation method and application thereof, the low-cobalt ternary positive electrode material comprising a low-cobalt ternary material base, a Co coating layer coated on the surface of the base, and a fast ion conductor coating layer coated on the surface of the Co coating layer; the preparation method comprises the following steps: proportionally mixing a precursor and a lithium source for the first time; in step 2, the mixed material is calcined for the first time; the sintered material is crushed for the first time to obtain a first intermediate material; the first intermediate material is added to a Co source for the second time to mix, calcine and crush to obtain a second intermediate material; and the second intermediate material is added to a coating source for the third time to mix, calcine and crush. The low-cobalt ternary positive electrode material is prepared by combining the low-Co-content base with the coating process, and the structure and electrochemical performance of the positive electrode material are optimized; the positive electrode material has the characteristics of low cobalt content and low impedance while maintaining the round single crystal, which is beneficial to improving the capacity and cycle performance of the ternary positive electrode material, and effectively reduces the preparation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and more specifically, to a low-cobalt ternary cathode material, its preparation method, and its application. Background Technology

[0002] In recent years, with the increasingly severe energy crisis and environmental pollution, new energy vehicles have developed rapidly. As the "heart" of new energy vehicles, lithium-ion batteries have been widely studied due to their high energy density, long cycle life, and environmental friendliness. Cathode materials, as an important component of lithium-ion batteries, are a key factor influencing the energy density and cycle life of lithium-ion batteries.

[0003] Existing technologies often use high-cobalt precursors and lithium hydroxide sintering to prepare ternary cathode materials. However, due to the high cobalt content of ternary precursors, the limited and expensive cobalt resources result in high preparation costs. High cobalt content also increases the amount of cobalt leaching during material cycling or storage, leading to material structural degradation and failure. Furthermore, conventional sintering processes result in ternary cathode materials with numerous defects and slightly inferior performance.

[0004] Therefore, there is an urgent need for a ternary cathode material that can reduce cobalt content and preparation costs while optimizing material structure and electrochemical performance.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing a low-cobalt ternary cathode material, its preparation method, and its applications. By combining a low-Co content matrix with a coating process, the structure and electrochemical performance of the cathode material are optimized. This cathode material maintains a rounded single crystal while also possessing low-cobalt / low-impedance characteristics, which is beneficial for improving the capacity and cycle performance of the ternary cathode material, while effectively reducing the preparation cost.

[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: A low-cobalt ternary cathode material includes a low-cobalt ternary material matrix, a Co coating layer covering the surface of the matrix, and a fast ion conductor coating layer covering the surface of the Co coating layer.

[0008] Furthermore, the chemical formula of the matrix is ​​Li. m Ni x Co y Mn z O2, where 0.65≤x≤0.85, 0.02≤y≤0.05, 0.1≤z≤0.3, x+y+z=1; preferably, 1.01≤m≤1.07.

[0009] Furthermore, the chemical formula of the matrix is ​​Li.a Ni b Co c Mn d M 1-b-c-d O2, wherein 0.65≤b<0.85, 0.02≤c<0.05, 0.1≤d<0.3, b+c+d<1; M element is a dopant element; preferably, 1.01≤a≤1.07.

[0010] Furthermore, the M element is selected from at least two of Zr, Mg, Al, Y, Nb, Ti, W, Ta, Sr, and La.

[0011] Furthermore, the matrix is ​​a low-cobalt ternary single crystal material with a particle size Dv50 of 3.0~4.0μm.

[0012] Furthermore, the Co coating layer comprises lithium cobalt oxide with a coating thickness of 0.1-0.35 μm.

[0013] Furthermore, the Co coating layer comprises a surface cobalt-rich LiCoO2 coating layer and a disordered rock salt phase layer.

[0014] Furthermore, the fast ion conductor coating layer includes at least two of Li2ZrO3, Li2WO4, LiLaO2, Li2MoO4, LiAlO2, LiNbO3, and Li2TiO3.

[0015] The preparation method of the above-mentioned low-cobalt ternary cathode material includes the following steps: Step 1: Mix the precursor containing Ni, Co, and Mn elements and the lithium source in a specific ratio. Step 2: Roast the mixture once; Step 3: Crush the sintered material once to obtain intermediate material; Step 4: Add the primary intermediate material to the Co source for secondary mixing and secondary roasting. After roasting, perform secondary crushing to obtain secondary intermediate material. Step 5: Add the secondary intermediate material to the coating source and mix and calcine three times to obtain the low cobalt ternary cathode material.

[0016] Furthermore, the lithium source mentioned in step 1 includes at least one of lithium hydroxide, lithium carbonate, and lithium nitrate.

[0017] Furthermore, the chemical formula of the precursor mentioned in step 1 is Ni x Co y Mn z (OH)2, where 0.65≤x≤0.85, 0.02≤y≤0.05, 0.1≤z≤0.3, and x+y+z=1.

[0018] Furthermore, the mixing speed for the first mixing step in step 1 is 800~1700 rpm.

[0019] Furthermore, in step 2, the first calcination is carried out in an oxygen atmosphere, and the total sintering time is 8~23h.

[0020] Furthermore, in step 1, a doping source is added in proportion, wherein the doping source is at least one of an oxide of element M, a hydroxide of element M, or an acidic compound of element M.

[0021] Furthermore, in step 2, the single sintering is carried out in stages, with high-temperature sintering first and low-temperature sintering second.

[0022] Furthermore, the particle size DV50 of the material after primary crushing in step 3 is 3.0~4.0μm.

[0023] Furthermore, the amount of Co source added in step 4 accounts for 1 to 4 mol of the amount of the primary intermediate material.

[0024] Furthermore, the coating source mentioned in step 5 includes at least two of the following: Zr source, Al source, Nb source, Ti source, W source, La source, and Mo source.

[0025] Furthermore, the sintering temperature in the high-temperature section is 900~940℃, the sintering time is 6~15h, and the heating rate is 2~4℃ / min.

[0026] Furthermore, the sintering temperature in the low-temperature section is 800~860℃, the sintering time is 2~8h, and the cooling rate from the high-temperature section sintering temperature to the low-temperature section sintering temperature is 2~4℃ / min.

[0027] Furthermore, the Co source mentioned in step 4 includes at least one of Co oxides and Co hydroxides.

[0028] Furthermore, in step 4, the roasting temperature is 700~830℃ and the roasting time is 5~10h.

[0029] Further, in step 5, the secondary intermediate material is added to coating source A, coating source B, and coating source C for three-stage mixing and calcination; the coating source A, coating source B, and coating source C are oxides or acid compounds of three different elements.

[0030] Further, the coating source A is an Al source, and the amount added accounts for 0.05%-0.3% of the mass of the secondary intermediate material; the coating source B is an Nb source, and the amount added accounts for 0.1%-0.3% of the mass of the secondary intermediate material; the coating source C is a Ti source, and the amount added accounts for 0.05%-0.3% of the mass of the secondary intermediate material.

[0031] Furthermore, in step 5, the roasting temperature is 400~550℃ and the roasting time is 5~12h.

[0032] The application of the above-mentioned low-cobalt ternary cathode material, or the above-mentioned preparation method, in the preparation of electric vehicles, electric bicycles, energy storage systems, or mobile storage devices.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The low-cobalt ternary cathode material of the present invention can effectively reduce the Co content and reduce the material preparation cost; by combining a low-Co matrix with a Co coating layer and a fast ion conductor coating layer, the material structure is optimized and excellent electrochemical performance is ensured while reducing costs, and it has the characteristics of high capacity and low impedance.

[0034] 2. The preparation method of the low-cobalt ternary cathode material of the present invention adopts a combination of low-cobalt precursor and lithium source and other raw materials for calcination, and through Co coating and low-temperature coating of fast ion conductor, the excellent structural performance and electrochemical performance of the cathode material are guaranteed while reducing costs.

[0035] 3. The preparation method of the low-cobalt ternary cathode material of the present invention adopts a low-cobalt precursor combined with a doping coating sintering process. While reducing the cobalt content and preparation cost, the prepared low-cobalt low-impedance single crystal material has both excellent material structure and electrochemical performance, and has the characteristics of high capacity and low impedance.

[0036] 4. The preparation method of the low-cobalt ternary cathode material of the present invention uses a low-cobalt precursor and optimizes the calcination and coating processes, which can reduce costs and give it excellent comprehensive performance. Through element doping and coating processes, secondary calcination and low-temperature annealing repair material defects and stabilize the interface structure. It can also improve the cathode material capacity, improve the material cycle performance, and optimize product performance. Attached Figure Description

[0037] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0038] Figure 1 The X-ray diffraction pattern of the cathode material prepared in the embodiments of the present invention; Figure 2 Cycle performance curves of the cathode material prepared in the embodiments of the present invention; Figure 3 This is a scanning electron microscope image of the positive electrode material prepared in Example 1 of the present invention. Detailed Implementation

[0039] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0040] Explanation of technical terms: Impedance: When a battery is working, the resistance that current encounters when flowing through the battery is divided into ohmic internal resistance and polarization internal resistance.

[0041] This invention provides a low-cobalt ternary cathode material, comprising a low-cobalt ternary material matrix and a Co coating layer covering the surface of the matrix. The coating layer can reduce residual alkali on the material surface, improve the electronic conductivity of the material, and improve impedance and cycle performance.

[0042] In some embodiments, the chemical formula of the matrix is ​​Li. m Ni x Co y Mn z O2, wherein 0.65≤x≤0.85, 0.02≤y≤0.05, 0.1≤z≤0.3, and x+y+z=1; preferably, 1.01≤m≤1.07, where m includes but is not limited to 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, and 1.07.

[0043] In some embodiments, the chemical formula of the matrix is ​​Li. a Ni b Co c Mn d M 1-b-c-d O2, wherein 0.65≤b<0.85, 0.02≤c<0.05, 0.1≤d<0.3, b+c+d<1; element M is a dopant element; preferably, 1.01≤a≤1.07, where a includes but is not limited to 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, and 1.07.

[0044] In some embodiments, the M element is selected from at least two of Zr, Mg, Al, Y, Nb, Ti, W, Ta, Sr, and La. The doping element mainly acts on the bulk phase of the material, embedding itself inside the material lattice to improve the crystal structure and interface electronic state. The elements combine with each other to improve the cation mixing degree, while avoiding structural collapse during delithiation of the material and improving the material's cycle performance.

[0045] In the prior art, the ternary precursor of ternary cathode materials has a high cobalt content. Cobalt resources are limited and expensive, resulting in high preparation costs. The low-cobalt ternary cathode material of this invention can effectively reduce the Co content and reduce the material preparation cost.

[0046] In some embodiments, the substrate is a low-cobalt ternary single crystal material with a particle size Dv50 of 3.0~4.0μm, including but not limited to 3.0μm, 3.2μm, 3.5μm, 3.6μm, 3.8μm, and 4.0μm.

[0047] In some embodiments, the Co coating layer comprises lithium cobalt oxide with a coating thickness of 0.1-0.35 μm, including but not limited to 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, and 0.35 μm. The Co source reacts with the residual lithium compound on the material surface to improve electronic conductivity and reduce impedance.

[0048] In some embodiments, the Co coating layer comprises a surface cobalt-rich LiCoO2 coating layer and a disordered rock salt phase layer. The disordered rock salt phase layer is formed by Ni-Co cation interdiffusion induced by a high-nickel / low-manganese bulk phase composition. Specifically, under high-temperature driving, the Co element coated on the matrix surface diffuses inward, while Ni in the matrix diffuses outward; this cation interdiffusion forms a disordered rock structure.

[0049] In some embodiments, the fast ion conductor coating layer includes at least two of Li2ZrO3, Li2WO4, LiLaO2, Li2MoO4, LiAlO2, LiNbO3, and Li2TiO3. By forming a fast ion conductor coating layer on the surface of the cathode material, the lithium ion transport channel can be expanded, lithium ion transport can be promoted, direct contact between the electrolyte and the cathode material can be suppressed, the surface structure of the material can be stabilized, and the product performance can be optimized.

[0050] The present invention relates to a low-cobalt ternary cathode material, which combines a low-cobalt matrix with a co-coating layer and a fast-ion conductor coating layer. This reduces costs while optimizing the material structure and ensuring excellent electrochemical performance. Through analysis of the cathode material's electrical performance data, it has been demonstrated that the low-cobalt ternary cathode material of the present invention possesses the characteristics of high capacity and low impedance.

[0051] A method for preparing a low-cobalt ternary cathode material includes the following steps: Step 1: Mix the precursor containing Ni, Co, and Mn elements and the lithium source in a specific ratio. Step 2: Roast the mixture once; Step 3: Crush the sintered material once to obtain intermediate material; Step 4: Add the primary intermediate material to the Co source for secondary mixing and roasting, and then perform secondary crushing to obtain secondary intermediate material; Step 5: Add the secondary intermediate material to the coating source for three mixing and calcination to obtain the finished low-cobalt ternary cathode material.

[0052] In some embodiments, the lithium source in step 1 includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, or other battery-grade lithium salts.

[0053] In some embodiments, the precursor in step 1 has the chemical formula Ni. x Co y Mn z (OH)2, where 0.65≤x≤0.85, 0.02≤y≤0.05, 0.1≤z≤0.3, and x+y+z=1.

[0054] The present invention discloses a method for preparing a low-cobalt ternary cathode material, which involves calcining a low-cobalt precursor with a lithium source, and using Co coating and low-temperature coating with fast ion conductors to reduce costs while ensuring the excellent structure and electrochemical performance of the cathode material. Analysis of the electrical performance data of the cathode material prepared by the present invention demonstrates that the low-cobalt ternary cathode material of the present invention has the characteristics of high capacity and low impedance.

[0055] In some embodiments, a doping source is added in step 1 in proportion, wherein the doping source is at least one of an oxide of element M, a hydroxide of element M, or an acidic compound of element M.

[0056] In some implementations, the mixing speed for one mixing step in step 1 is 800~1700 rpm, for example 800 rpm, 1000 rpm, 1200 rpm, 1500 rpm, or 1700 rpm.

[0057] The present invention discloses a method for preparing low-cobalt ternary cathode materials, which involves uniformly mixing nickel-cobalt-manganese hydroxide, lithium source, and dopant source raw materials under high-speed stirring, and employing a low-cobalt precursor combined with a doping coating sintering process. This method reduces the cobalt content and preparation cost while producing a low-cobalt, low-impedance single-crystal material with excellent material structure and electrochemical performance.

[0058] In some embodiments, the first calcination in step 2 is sintering in an oxygen atmosphere, and the total sintering time is 8 to 23 hours, including but not limited to 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, and 23 hours.

[0059] In some embodiments, the single calcination in step 2 employs segmented sintering, first performing high-temperature sintering and then low-temperature sintering. This invention utilizes a high-low temperature platform for sintering, combined with doping and coating processes, to fully leverage the performance of the low-cobalt ternary cathode material.

[0060] Furthermore, the sintering temperature in the high-temperature section is 900~940℃, the sintering time is 6~15h, for example 6h, 8h, 9h, 10h, 12h, 15h, and the heating rate is 2~4℃ / min, for example 2℃ / min, 3℃ / min, 4℃ / min.

[0061] Furthermore, the sintering temperature in the low-temperature section is 800~860℃, the sintering time is 2~8h, and the cooling rate from the high-temperature section sintering temperature to the low-temperature section sintering temperature is 2~4℃ / min, for example 2℃ / min, 3℃ / min, 4℃ / min.

[0062] In some implementations, the particle size Dv50 of the material after primary crushing in step 3 is 3.0~4.0μm, including but not limited to 3.0μm, 3.2μm, 3.5μm, 3.6μm, 3.8μm, and 4.0μm.

[0063] In some embodiments, the amount of Co source added in step 4 accounts for 1 to 4 mol of the amount of the primary intermediate material, including but not limited to 1 mol%, 2 mol%, 3 mol%, and 4 mol.

[0064] In some embodiments, the Co source in step 4 includes at least one of an oxide of Co and a hydroxide of Co.

[0065] In some embodiments, the secondary roasting temperature in step 4 is 700~830℃, including but not limited to 700℃, 720℃, 750℃, 760℃, 780℃, 800℃, and 830℃, and the roasting time is 5~10h, including but not limited to 5h, 6h, 7h, 8h, 9h, and 10h.

[0066] In some embodiments, the coating source in step 5 includes at least two of the following: Zr source (zirconium oxide, zirconium acid compound), Al source (aluminum oxide, aluminum acid compound), Nb source (niobium oxide, niobium acid compound), Ti source (titanium oxide, titanium acid compound), W source (tungsten oxide, tungsten acid compound), La source (lanthanum oxide, lanthanum acid compound), and Mo source (molybdenum oxide, molybdenum acid compound). The residual Li2CO3 on the surface of the cathode material is mixed with the Zr, Al, Nb, Ti, W, La, or Mo source, and a low-temperature calcination reaction is carried out to generate Li2ZrO3, LiAlO2, LiNbO3, Li2TiO3, Li2WO4, LiLaO2, or Li2MoO4, respectively. This forms a fast ion conductor coating layer on the surface of the cathode material, which can expand the lithium-ion transport channel, promote lithium-ion transport, inhibit direct contact between the electrolyte and the cathode material, stabilize the material surface structure, and optimize product performance.

[0067] In some embodiments, step 5 involves adding the secondary intermediate material to coating source A, coating source B, and coating source C for three rounds of mixing and three rounds of calcination. The coating source A, coating source B, and coating source C are oxides or acid compounds of three different elements.

[0068] Further, coating source A is an Al source (aluminum oxide, aluminum acid compound), added at 0.05%-0.3% of the secondary intermediate material mass; coating source B is an Nb source (niobium oxide, niobium acid compound), added at 0.1%-0.3% of the secondary intermediate material mass; and coating source C is a Ti source (titanium oxide, titanium acid compound), added at 0.05%-0.3% of the secondary intermediate material mass. Different types of coating source elements have different effects on the material's capacitance and impedance, and the amount of coating source used corresponds to the type of element.

[0069] In some embodiments, the calcination temperature in step 5 is 400~550℃, including but not limited to 400℃, 420℃, 450℃, 480℃, 500℃, and 550℃, and the calcination time is 5~12h, including but not limited to 5h, 6h, 8h, 9h, 10h, and 12h. This three-calcination process achieves low-temperature coating of Al / Nb / Ti elements. The residual Li2CO3 on the surface of the cathode material is mixed with the Al, Nb, and Ti sources, and calcined at temperatures above 400℃ to generate LiAlO2, LiNbO3, and Li2TiO3, respectively. This forms a LiAlO2 / LiNbO3 / Li2TiO3 fast ion conductor coating layer on the surface of the cathode material, which can expand the lithium-ion transport channels, promote lithium-ion transport, inhibit direct contact between the electrolyte and the cathode material, stabilize the material surface structure, and optimize product performance.

[0070] The present invention discloses a method for preparing low-cobalt ternary cathode materials. By using low-cobalt precursors and optimizing the calcination and coating processes, the method can reduce costs while achieving excellent overall performance. Through elemental doping and coating processes, secondary calcination and low-temperature annealing repair material defects and stabilize the interface structure. This method can also improve the cathode material capacity, enhance the material cycle performance, and optimize product performance.

[0071] The above-mentioned low-cobalt ternary cathode material, or the above-mentioned preparation method, can be used in the preparation of electric vehicles, electric bicycles, energy storage systems, or mobile storage devices.

[0072] Example 1 A method for preparing a low-cobalt ternary cathode material includes the following steps: S1, based on the chemical formula of the matrix Li 1.06 Ni 0.80 Co 0.05 Mn 0.15 O2 is used to mix the precursor Ni in a certain proportion 0.83 Co 0.02 Mn 0.15 (OH)2 and lithium hydroxide are added to a high-speed mixer and mixed once at a speed of 1200 rpm for 45 minutes. S2. The mixture obtained in step S1 is calcined once in a box furnace with an oxygen concentration of 99% (segmented sintering, first sintering in the high-temperature section, then sintering in the low-temperature section). The sintering temperature of the high-temperature section is 910℃, the heating rate is 2℃ / min, and the sintering time is 10h. The sintering temperature of the low-temperature section is 820℃, the cooling rate from the high-temperature section sintering temperature to the low-temperature section sintering temperature is 2℃ / min, and the sintering time is 6h. S3. The sintered material obtained in step S2 is crushed to a particle size of Dv50=3.5μm using an airflow crushing device. After sieving, a primary intermediate material is obtained, namely low cobalt ternary single crystal material. S4. Add 3.5%mol of Co source to the primary intermediate material obtained in step S3 for secondary mixing, calcine at 720℃ for 8 hours, and crush to a particle size Dv50=3.5μm to obtain secondary intermediate material. S5. The secondary intermediate material obtained in step S4 is mixed three times with coating source Al oxide (0.1% of the mass of the secondary intermediate material), coating source Nb oxide (0.2% of the mass of the secondary intermediate material), and coating source Ti oxide (0.05% of the mass of the secondary intermediate material). The mixture is then calcined three times at 400℃ for 8 hours. After sieving, the low cobalt ternary cathode material is obtained.

[0073] Example 2 The difference between this embodiment and Embodiment 1 is that: S1, based on the chemical formula of the matrix Li1.06 (Ni 0.80 Co 0.05 Mn 0.15 ) 0.9925 Zr 0.0025 Al 0.004 W 0.001 O2 is used to mix the precursor Ni in a certain proportion 0.83 Co 0.02 Mn 0.15 (OH)2, lithium hydroxide, and the dopant source were added to a high-speed mixer and mixed once at 1200 rpm for 45 minutes. The rest was the same as in Example 1.

[0074] Example 3 The difference between this embodiment and Embodiment 2 is that the sintering time in the high-temperature section in step S2 is 12 hours, and the sintering time in the low-temperature section is 4 hours. The rest is the same as in Embodiment 2.

[0075] Example 4 The difference between this embodiment and Embodiment 2 is that the sintering time in the high-temperature section in step S2 is 8 hours, and the sintering time in the low-temperature section is 8 hours. The rest is the same as in Embodiment 2.

[0076] Example 5 The difference between this embodiment and Embodiment 2 is that the sintering temperature of the high-temperature section in step S2 is 900℃, and the sintering temperature of the low-temperature section is 850℃. Everything else is the same as in Embodiment 2.

[0077] Example 6 The difference between this embodiment and Embodiment 2 is that: S1, based on the chemical formula of the matrix Li 1.06 (Ni 0.80 Co 0.05 Mn0. 15 ) 0.9935 Zr 0.0025 Al 0.004 O2 is used to mix the precursor Ni in a certain proportion 0.83 Co 0.02 Mn 0.15 (OH)2, lithium hydroxide, and the dopant source were added to a high-speed mixer and mixed once at 1200 rpm for 45 minutes. The rest was the same as in Example 2.

[0078] Example 7 The difference between this embodiment and Embodiment 2 is that in step S4, the food is calcined at 740°C for 8 hours. The rest is the same as in Embodiment 2.

[0079] Example 8 The difference between this embodiment and Embodiment 2 is that in step S5, the secondary intermediate material obtained in step S4 is mixed three times with coating source Al oxide (0.2% of the secondary intermediate material by mass), coating source Nb oxide (0.3% of the secondary intermediate material by mass), and coating source Ti oxide (0.1% of the secondary intermediate material by mass). The rest is the same as in Embodiment 2.

[0080] Comparative Example 1 The difference between this comparative example and Example 2 is that step S4 is omitted. The rest is the same as Example 2.

[0081] Comparative Example 2 The difference between this comparative example and Example 2 is that step S5 is omitted. The rest is the same as Example 2.

[0082] Experimental example: I. The X-ray diffraction pattern of the cathode material prepared in the embodiments of the present invention is as follows: Figure 1 As shown in the figure, #74-0919 is the standard card.

[0083] Figure 1 The XRD pattern of the cathode material prepared according to the embodiments of the present invention is shown in the figure, which shows that the cathode material prepared according to the embodiments of the present invention has good crystallinity.

[0084] II. Electrochemical performance testing was conducted on the positive electrode materials prepared in the embodiments and comparative examples of this invention to prepare coin cells: the mass ratio of active material (positive electrode material prepared in the examples): conductive agent (carbon black): binder (PVDF) in the positive electrode was 90:5:5; lithium was used as the negative electrode. The electrochemical performance test results are shown in Tables 1 and 2. Figure 2 As shown.

[0085] The manufacturing and testing of button cells mainly consists of the following processes: material preparation, coating, baking, pressing, stamping, assembly, and testing. (1) Ingredient preparation: Add the positive electrode material, carbon black, PVDF and solvent NMP to a beaker according to the set ratio and stir with a stirrer to form a uniform slurry. Control the amount of NMP added so that its fluidity is similar to that of glue. (2) Coating: The slurry is evenly coated onto the aluminum foil using a coater; (3) Baking: Bake the coated electrode at 120°C for 2 hours in a vacuum oven. (4) Tableting: After the edges of the baked electrode are neatly trimmed, the electrode is placed into a tablet press and compacted with a pressure of 30MPa. (5) Punching: Cut 5-10 small round pieces from the pressed electrode sheet in the cutting sheet, and at the same time cut 5-10 comparison samples of uncoated foil. After weighing, select 5 small round pieces with qualified weight. (6) Assembly: Assembly is carried out in a glove box filled with dry nitrogen. The water vapor and oxygen content is less than 0.1 ppm. Place the qualified small round pieces into the positive electrode side of the button cell shell with the gasket placed in advance, with the coated side facing away from the positive electrode. Then drop 2 drops of electrolyte (lithium hexafluorophosphate) onto the positive electrode piece, then place the separator and drop 1~2 drops of electrolyte, then place the pure lithium sheet, gasket, and spring, and finally place the negative electrode side shell of the button cell. After assembly, seal the shell with a sealing machine. (7) Test: Calculate the active material content based on the weight of the weighed small discs, and calculate the charge and discharge current required for coining based on the estimated active material capacity, and conduct charge and discharge tests.

[0086] Table 1. Initial charge-discharge capacity of the cathode materials prepared in the examples and comparative examples at 0.1C and 2.5~4.45V.

[0087] Table 2. Pulse DCR at -10℃ for the cathode materials prepared in the examples and comparative examples at 0.1C and 2.5~4.45V.

[0088] As shown in Tables 1 and 2, comparing Examples 2 / 3 / 4 / 5 / 6 reveals that appropriate temperatures and times in the first high-temperature calcination and the second low-temperature calcination have no significant impact on sample volume, and the pulse impedance data are basically consistent. The process of combining segmented high-temperature calcination to form a layered structure with low-temperature calcination to repair defects in the second stage ensures the integrity of the material structure.

[0089] Compared with Example 2 and Example 6, the matrix of Example 2 was further doped with W element. The dopant element occupies the transition metal site, stabilizes the layered structure, effectively improves the material capacity, and reduces the pulse impedance. This is mainly because the M element occupying the transition metal site can form strong MO bonds, optimize the grain morphology and size, and promote the Li interface. + The transmission.

[0090] In this invention, the cathode material matrix and the Co coating layer on the matrix surface form a Co concentration-structure dual gradient framework. The Co-enriched surface can significantly improve the electronic conductivity of the electrode layer and effectively reduce the interfacial impedance. At the same time, the Co coating layer can reduce the residual lithium compounds on the surface of the cathode material with resistive characteristics, further reducing the lithium-ion transport impedance.

[0091] In this embodiment of the invention, Al / Nb / Ti elements are coated onto the surface of the Co coating layer through three low-temperature calcination processes, forming a LiAlO2 / LiNbO3 / Li2TiO3 fast ion conductor coating layer on the surface of the cathode material, thereby promoting lithium ion transport.

[0092] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low-cobalt ternary cathode material, characterized in that, The material includes a low-cobalt ternary material matrix, a Co coating layer covering the surface of the matrix, and a fast ion conductor coating layer covering the surface of the Co coating layer.

2. The low-cobalt ternary cathode material according to claim 1, characterized in that, The chemical formula of the matrix is ​​Li m Ni x Co y Mn z O2, where 0.65≤x≤0.85, 0.02≤y≤0.05, 0.1≤z≤0.3, x+y+z=1; preferably, 1.01≤m≤1.

07.

3. The low-cobalt ternary cathode material according to claim 1, characterized in that, The chemical formula of the matrix is ​​Li a Ni b Co c Mn d M 1-b-c-d O2, wherein 0.65≤b<0.85, 0.02≤c<0.05, 0.1≤d<0.3, b+c+d<1; M element is a dopant element; preferably, 1.01≤a≤1.

07.

4. The low-cobalt ternary cathode material according to claim 3, characterized in that, The element M is selected from at least two of Zr, Mg, Al, Y, Nb, Ti, W, Ta, Sr, and La.

5. The low-cobalt ternary cathode material according to claim 1, characterized in that, It should include at least one of the following technical features: (1) The matrix is ​​a low-cobalt ternary single crystal material with a particle size Dv50 of 3.0~4.0μm; (2) The Co coating layer comprises lithium cobalt oxide with a coating thickness of 0.1-0.35 μm; (3) The Co coating layer includes a surface cobalt-rich LiCoO2 coating layer and a disordered rock salt phase layer; (4) The fast ion conductor coating layer includes at least two of Li2ZrO3, Li2WO4, LiLaO2, Li2MoO4, LiAlO2, LiNbO3 and Li2TiO3.

6. The method for preparing the low-cobalt ternary cathode material according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1: Mix the precursor containing Ni, Co, and Mn elements and the lithium source in a specific ratio. Step 2: Roast the mixture once; Step 3: Crush the sintered material once to obtain intermediate material; Step 4: Add the primary intermediate material to the Co source for secondary mixing and secondary roasting. After roasting, perform secondary crushing to obtain secondary intermediate material. Step 5: Add the secondary intermediate material to the coating source and mix and calcine three times to obtain the low cobalt ternary cathode material.

7. The method for preparing the low-cobalt ternary cathode material according to claim 6, characterized in that, It should include at least one of the following technical features: (1) The lithium source mentioned in step 1 includes at least one of lithium hydroxide, lithium carbonate, and lithium nitrate; (2) The chemical formula of the precursor mentioned in step 1 is Ni x Co y Mn z (OH)2, where 0.65≤x≤0.85, 0.02≤y≤0.05, 0.1≤z≤0.3, x+y+z=1; (3) The mixing speed for the first mixing in step 1 is 800~1700 rpm; (4) In step 2, the first calcination is carried out in an oxygen atmosphere and the total sintering time is 8~23h.

8. The method for preparing the low-cobalt ternary cathode material according to claim 7, characterized in that, It should include at least one of the following technical features: (1) In step 1, a doping source is also added in proportion, wherein the doping source is at least one of the following: an oxide of element M, a hydroxide of element M, and an acidic compound of element M; (2) In step 2, the first firing adopts segmented sintering, first sintering the high-temperature section, and then sintering the low-temperature section; (3) The particle size DV50 of the material after the first crushing in step 3 is 3.0~4.0μm; (4) The amount of Co source added in step 4 accounts for 1 to 4 mol% of the amount of the primary intermediate material. (5) The coating source mentioned in step 5 includes at least two of the following: Zr source, Al source, Nb source, Ti source, W source, Ta source, and Mo source.

9. The method for preparing the low-cobalt ternary cathode material according to claim 8, characterized in that, It should include at least one of the following technical features: (1) The sintering temperature of the high-temperature section is 900~940℃, the sintering time is 6~15h, and the heating rate is 2~4℃ / min; (2) The sintering temperature of the low-temperature section is 800~860℃, the sintering time is 2~8h, and the cooling rate from the high-temperature section sintering temperature to the low-temperature section sintering temperature is 2~4℃ / min; (3) The Co source mentioned in step 4 includes at least one of the oxides of Co and the hydroxides of Co; (4) The roasting temperature in step 4 is 700~830℃ and the roasting time is 5~10h; (5) In step 5, the secondary intermediate material is added to coating source A, coating source B and coating source C for three mixing and calcination; the coating source A, the coating source B and the coating source C are oxides or acid compounds of three different elements. (6) The coating source A is an Al source, and the amount added accounts for 0.05%-0.3% of the mass of the secondary intermediate material; the coating source B is an Nb source, and the amount added accounts for 0.1%-0.3% of the mass of the secondary intermediate material; the coating source C is a Ti source, and the amount added accounts for 0.05%-0.3% of the mass of the secondary intermediate material. (7) The roasting temperature in step 5 is 400~550℃ and the roasting time is 5~12h.

10. The application of the low-cobalt ternary cathode material according to any one of claims 1 to 5, or the preparation method according to any one of claims 6 to 9, in the preparation of electric vehicles, electric bicycles, energy storage systems, or mobile storage devices.